2018
DOI: 10.1186/s12885-018-4939-8
|View full text |Cite
|
Sign up to set email alerts
|

Preadmission antidepressant use and bladder cancer: a population-based cohort study of stage at diagnosis, time to surgery, and surgical outcomes

Abstract: BackgroundAmong cancer patients, prior antidepressant use has been associated with impaired survival. This could be due to differences in stage at diagnosis, in receipt of treatment, or in treatment complications. The purpose of this study was, therefore, to examine if preadmission antidepressant use in patients with bladder cancer is associated with tumor stage at diagnosis, rate of cystectomy, and surgical outcomes, including survival.MethodsWe performed a registry-based cohort study including all patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…In our review, there was only one study investigating the possible associations between antidepressants (including SSRIs, SNRIs, MAOIs, and TCA) and invasive bladder cancer [14]. Steffensen et al performed a national population-based cohort study in Denmark enclosing all cases with invasive bladder cancer during 2005-2015 [14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our review, there was only one study investigating the possible associations between antidepressants (including SSRIs, SNRIs, MAOIs, and TCA) and invasive bladder cancer [14]. Steffensen et al performed a national population-based cohort study in Denmark enclosing all cases with invasive bladder cancer during 2005-2015 [14].…”
Section: Discussionmentioning
confidence: 99%
“…In our review, there was only one study investigating the possible associations between antidepressants (including SSRIs, SNRIs, MAOIs, and TCA) and invasive bladder cancer [14]. Steffensen et al performed a national population-based cohort study in Denmark enclosing all cases with invasive bladder cancer during 2005-2015 [14]. The results showed that antidepressants use as a whole in the year before cancer diagnosis was associated with less advanced cancer at diagnosis (aOR = 0.86, 95% CI = 0.74-0.99) [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations